Tailoring hot carrier cooling and recombination dynamics of mixed halide perovskite by incorporating Au@CZTS core–shell nanocrystal. (6th October 2021) - Prodhan, Sayan; Chauhan, Kamlesh Kumar; Karmakar, Manobina; Ghosh, Anima; Bhattacharyya, Sayan; Datta, Prasanta Kumar
Abstract: Organic–inorganic halide perovskite has emerged as the front-runner of absorber materials for highly efficient solar cell in recent years. The incorporation of metallic (Au, Ag) nanoparticles (NPs) within the perovskite contributes to the effective tuning of their optoelectronic properties via enhancing the channels of solar energy transfer and promoting carrier transport. Placing a dielectric shell over the metal NP further enhances the carrier mobility and reduces the carrier recombination in the semiconductor material. Here, we have extensively investigated the effect of the Au@CZTS core–shell nanocrystal (NC) on hot carrier (HC) cooling dynamics and excited carrier recombination dynamics in bulk MAPbI3− X Cl X perovskite using femtosecond transient absorption spectroscopy with a temporal and spectral resolution of 120 fs and 0.8 nm respectively. The HC cooling dynamics indicates the formation of longitudinal optical (LO) phonons within the first 0.6 ps and a delayed conversion of LO phonons to longitudinal acoustic (LA) phonons from 8 ps to 15.9 ps due to the incorporation of the Au@CZTS core–shell NC in bulk perovskite. Further, the investigation of carrier recombination dynamics shows that at a fixed pump fluence of 3.19 μ J cm −2 the rate constants decrease nearly 1 order of magnitude for (a) Auger recombination (from 1.2 × 10 −32  cm 6 s −1 to 1.7 × 10 −34 cm 6 s −1 ), (b) band-to-band recombination (from 8 × 10 −14  cm 3 s −1 to 8 × 10 −15 cm 3 s −1 ) and (c) trap state recombination (from 5.5 × 10 8 μ s −1 to 5 × 10 7 μ s −1 ) after the modification of bulk perovskite by Au@CZTS core–shell NC. Delayed conversion of LO phonons to LA phonons confirms the presence of an enhanced 'hot phonon bottleneck' effect in modified bulk perovskite. Lowering of the recombination rate constants provides an opportunity for developing high-performance perovskite-based photovoltaics.